Study of Laboratory Diagnosis of Colibasilosis Infection In Local Hen In Surabaya - Rondius Solfaine; Indra Rahmawati; Kurnia Desiandura; Yuriska Yuriska (Journal of Applied Veterinary Science And Technology, 2023)
Background: On November 18, 2022, euthanasia and hen necropsy were conducted (protocol number A-164) in the veterinary pathology laboratory, Faculty Of Veterinary Medicine, Wijaya Kusuma University Surabaya. The hen belongs to a local farmer located at Sawahan, Surabaya. Based on the anamnesis, it is known that the hen was four months old and weighed 1.4 kg. The population consists of eight birds, and one of them was sick, never treated or vaccinated, in a cage made of bamboo, corn fodder, rice bran, and drinking water from tap water. Clinical symptoms show a decreased appetite for the last day, watery eyes, runny nose, lethargy, and diarrhea with feces green mixed with white colors. The initial diagnosis of the chicken was infected with Salmonella sp. with a differential diagnosis of Escherichia coli. Purpose: To diagnose bacterial disease in local chickens with a pathological examination, parasitological examination, microbiological isolation, and clinical pathology for hematology. Result: The results of the anatomic pathology examination showed that the chickens had hemorrhagic tracheitis, hemorrhagic necrotic pneumonia, hemorrhagic necrotic enteritis, hemorrhagic necrotic hepatitis, and hemorrhage in the proventriculus. Parasite identification was found in Raillietina sp. and Ornithonyssus sylviarum. Isolation of bacteria was found in Escherichia coli from the duodenum organ. The chickens had hypoproteinemia, poikilocytosis teardrop and rouleaux, leukocytosis with heterophilia, and monocytosis. Conclusion: Based on the examination associated with the results of anamnesis and examination of clinical symptoms, the chickens were diagnosed with Escherichia coli infection together with Raillietina sp. and Ornithonyssus sylviarum infestations.